The study of conventional partial discharge measurement for gas insulated line - Pattanadech, Norasage; Houngtaisong, Chakkri; Wichakul, Chalantorn; Thanormsakdomrong, Narinnitiporn; Monklang, Natthanon; Nganpitak, Tritod (My University, 2019)
Partial discharge (PD) measurement is one of the insulation diagnosis tools used for diagnosis the condition of the high voltage apparatus. Generally, PD is generated at the highly electric field stress site in the insulation system. This research focuses on PD measurement in a gas-insulated line (GIL) by using the conventional PD measurement. The 230kV, 2500A, single phase, GIL with 2.5m length was setup and used for experiments. In this paper, the experiments were divided into 4 cases, according to the types of artificial protrusions, i.e. 1) a protrusion on the high voltage conductor 2) a protrusion on the enclosure and 3) two protrusions on both conductor and enclosure. 4) a protrusion on the conductor covered by insulation compartment. The lengths of protrusions were varied. The results of experiment were presented with the phase resolved partial discharge patterns.
Keywords: Gas-insulated line; Partial discharge; Phase resolved partial discharge